An evaluation of the controversial Ethiopian anti-terrorism law - Dersolegn, Yeneabt Mekonen (African journal of law and criminology, 2015)
This paper strives to assess whether the critiques/ fears against the Ethiopian anti-terrorism law particularly on its substantive part are legitimate and acceptable in light of the FDRE constitution and different criminal law principles and policies. Therefore, the paper concludes that the criticisms/fears on substantive part of the law by different bodies are legitimate and acceptable. More specifically, the paper argues that, (1) the definition of terrorism in this specific law is antithetical to the principle of legality, (2) the law excessively stifles both freedom of expression and peaceful political dissents, (3) the criminalization of inchoate crimes other than attempt is not justifiable and acceptable, (4) The extents and the kinds of punishments are not proportional that are not complied with the constitutional prohibition of cruel, inhuman and degrading punishments. Accordingly, the paper urges the Ethiopian legislative body to amend the law in a way that avoids these short comings thereby to respect human rights while preventing terrorism.